The Effect Of Using Beyond Failure Strategies In Some General Physical Abilities For Junior Boxers - Jabbar, Abdul Jaleel (Journal of Physical Education, 2015)
The problem of this research can be seen in: most of the training programs do not give great attention to the development of general physical training abilities , the aim of research is to use Beyond Failure Strategies to develop Some General Physical Abilities for junior boxers . the hypotheses of research: is there a significant differences between pre and post tests for both groups, and between the post tests for the two groups. The sample of the research was 20 players divided into two groups standard and experimental, and through research procedures and the applied of the training program and conducting statistical procedures, researcher found that Beyond Failure Strategies are a way of positive impact in the development of elements of physical fitness. The development of the physical abilities to be used in the event of Beyond Failure Strategies to post and researcher recommended the need to use the Beyond Failure Strategies to develop general fitness and special physical abilities